Spotlight on coarse sediments: Comparative characterization of a poorly investigated seafloor biotope in the German Bight (SE North Sea). (30th September 2022) - Gutow, Lars; Gusky, Manuela; Beermann, Jan; Gimenez, Luis; Pesch, Roland; Bildstein, Tim; Heinicke, Kathrin; Ebbe, Brigitte
Abstract: Extensive marine benthos surveys have resulted in a solid understanding of the broad distribution pattern of seafloor biotopes in the southeastern North Sea (temperate northeast Atlantic region). However, due to the low spatial resolution of large-scale surveys, specific smaller-scale biotopes with scattered distribution have been insufficiently captured. Consequently, knowledge regarding the environmental characteristics and species inventories of some specific biotopes is still limited. We investigated the habitat characteristics and the macro-infauna (i.e., organisms in samples collected by a sediment grab and retained in a sieve with a mesh size of 1000 μm) of a spatially restricted, patchy coarse sediment (i.e., grain size fraction >500 μm accounting for ≥60% of the total sample mass) biotope in the German Bight over three consecutive years. Habitat and faunal characteristics were contrasted with four other benthic biotopes sampled at the same time to allow for a comparative evaluation. Our study revealed considerable fluctuations in grain size distribution among samples of the coarse sediment, potentially resulting from a frequent redistribution of sediments. A total number of 243 infauna taxa were identified at the 66 stations sampled over three consecutive years (16–33 stations per year) with a considerable proportion of endangered and rare species. The results highlight that previous studies have underestimated the species richness of the biotope. The focus on this previously poorly studied biotope type allowed us to detect species in the study region that were formerly unreported. The macro-infauna in the coarse sediments was characterized by comparatively high abundance and biomass, which may provide a rich food resource for organisms from higher trophic levels. Therefore, coarse sediments likely are an ecologically valuable seafloor biotope despite its limited coverage. Graphical abstract: Image 1 Highlights: Comprehensive description of a coarse sediment biotope in the SE North Sea. Identification of a hitherto underestimated benthic biodiversity. Benthic community with a high proportion of rare and endangered species. Identification of polychaete species yet unrecorded from the SE North Sea.